Profil Senyawa Volatil Minyak Atsiri Daun Serai Wangi dan Serai Dapur serta Uji Potensinya sebagai Bioaditif Solar - Sya'rifa Salma Musliyati Putri (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
The development of natural additives has become one of the alternative approaches to improve diesel fuel quality, particularly in terms of physical characteristics and ignition quality. This study aimed to analyze the volatile compounds of essential oils extracted from citronella leaves (Cymbopogon nardus (L.) Rendle) and lemongrass leaves (Cymbopogon citratus (DC.) Stapf), as well as to evaluate their potential as bioadditives for diesel fuel. The essential oils were obtained through hydrodistillation and subsequently characterized based on yield, water content, density, viscosity, and volatile compounds using Gas Chromatography–Mass Spectrometry (GC–MS). The essential oils were then blended with diesel fuel at concentrations of 0.2, 0.4, 0.6, 0.8, and 1.0% (v/v). The resulting blends were evaluated based on density, kinematic viscosity, distillation characteristics, and ignition quality through the Calculated Cetane Index (CCI). The results showed that citronella and lemongrass essential oils had different volatile compounds. Generally, the addition of both essential oils increased the density, kinematic viscosity, and CCI values of the diesel fuel blends, while all blends remained within the quality specification range for diesel fuel. The increase in CCI indicated a potential improvement in fuel ignition quality, which was presumably related to the presence of oxygenated compounds in the essential oils. Based on the evaluation results, the optimum concentrations were obtained at 0.8% (v/v) for citronella essential oil and 0.6% (v/v) for lemongrass essential oil. Overall, this study demonstrated that the volatile compounds of essential oils play an important role in determining their effects on the physical characteristics and ignition quality of diesel fuel, indicating their potential for further development as bioadditives for diesel fuel.
Approved by Teddy
Keywords: bioadditive; diesel fuel; essential oil; GC–MS; Calculated Cetane Index (CCI)